Using of Interpretive Structural Modeling Technique to Design a Technological Learning Model Focused on Emerging Metaverse Technology for Schools - Mansoor Forozanmehr; Abdollah Aliesmaeili; Kourosh Ghasemzadeh (Iranian Journal of Educational Research)
Objective: Metaverse has gained increasing interest in education, with much of literature focusing on its great potential to enhance both individual and social aspects of learning. This study aimed to design a technological learning model focused on emerging metaverse technology for schools in Iran in 2024. Methods: The research was conducted using a mixed methods approach (qualitative-quantitative), with the target group consisting of experts in educational sciences and information technology. In the qualitative part, data was collected through in-depth interviews based on focus groups and analyzed using thematic analysis and grounded theory. In the quantitative part, the interpretative structural model was used. Results: The qualitative findings included a systematic theoretical model that identifies causal, strategic, contextual, intervening and consequential factors. In the quantitative part, a structural interpretation model was categorized into three levels. All factors included in the model were statistically significant, with p-values ranging from <0.001 to 0.04, confirming the validity and reliability of the hierarchical structure. The driving factors at the first level included the creation of interactive and technological educational environments and the development and strengthening of skills. The enabling factors at the second level included assessing and improving educational progress, the digital revolution in education and learning, and optimizing teachers and administration. The outcome factors identified at the third level were skills development and teacher training, innovation and progress in management and education, process improvement and optimization, educational development and empowerment, and transformation in education and learning.